2008
DOI: 10.1677/jme-08-0025
|View full text |Cite
|
Sign up to set email alerts
|

Developmental origins of disease and determinants of chromatin structure: maternal diet modifies the primate fetal epigenome

Abstract: Chromatin structure is epigenetically altered via covalent modifications of histones to allow for heritable gene regulation without altering the nucleotide sequence. Multiple lines of evidence from rodents have established a role for epigenetic remodeling in regulating gene transcription in response to an altered gestational milieu. However, to date, it is unknown whether variations in the intrauterine environment in primates similarly induce changes in key determinants of hepatic chromatin structure. We hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
296
2
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(323 citation statements)
references
References 46 publications
18
296
2
7
Order By: Relevance
“…We have also confirmed that the epigenome may be sensitive to this form of dietary challenge during the suckling phase in rodents. This corresponds with work demonstrating that high-fat diets can impact upon histone acetylation and DNA methylation in rodents and macaques (Aagaard-Tillery et al 2008, Vucetic et al 2010.…”
Section: Discussionsupporting
confidence: 87%
“…We have also confirmed that the epigenome may be sensitive to this form of dietary challenge during the suckling phase in rodents. This corresponds with work demonstrating that high-fat diets can impact upon histone acetylation and DNA methylation in rodents and macaques (Aagaard-Tillery et al 2008, Vucetic et al 2010.…”
Section: Discussionsupporting
confidence: 87%
“…Epigenetics comprises, among other more technically challenging methods, the investigation of DNA methylation profiles as the primary mark of environmentally mediated changes to gene expression. While the exact role of epigenetic mechanisms in fetal programming of metabolic diseases and body weight regulation remains to be further investigated, a number of animal models have demonstrated a causal relationship between early nutrition and later metabolic phenotype with gene dysregulation mediating such adverse metabolic outcomes (58)(59)(60)(61)(62) . A recently published article reviews the scientific evidence base of the association between the role of epigenetics in the fetal programming of adverse metabolic outcomes concluding that despite a vast amount of epigenomic data generated, the challenge still is to decipher the biological and clinical relevance of these epigenetic changes (63) .…”
Section: Epigenetics and Metabolomicsmentioning
confidence: 99%
“…A similar study was performed by Aagaard-Tillery et al (2008) in primate fetuses whose mothers were exposed during pregnancy to a control diet or a diet rich in fat. High fat intake led to an increase in triglycerides and the development of a fatty liver in the fetuses.…”
Section: Transgenerational Inheritancementioning
confidence: 95%